RESOURCE DEPENDENCE PERSPECTIVE DALAM TEORI ORGANISASI: (Telaah Konsepsual dan Isu Metoda Penelitian) (Fokus Ekonomi, 2009)
This article discussed about resource dependence perspective, which is explain that organizations have to acquire some critical resources for organization survival. Organizational design and structure was determined by environment change which is always uncertainty. To reduce this uncertainty, organization develop inter organizational linkage with the other organization. Merger, joint venture, and interlock directorates are some of the varieties. This article also discussed about conceptual and research issues in the resource dependence. Implications for future research and theory development are discussed.